2011
DOI: 10.4269/ajtmh.2011.11-0178
|View full text |Cite
|
Sign up to set email alerts
|

Community Case Management of Childhood Diarrhea in a Setting with Declining Use of Oral Rehydration Therapy: Findings from Cross-Sectional Studies among Primary Household Caregivers, Kenya, 2007

Abstract: Abstract. We sought to determine factors associated with appropriate diarrhea case management in Kenya. We conducted a cross-sectional survey of caregivers of children < 5 years of age with diarrhea in rural Asembo and urban Kibera. In Asembo, 61% of respondents provided oral rehydration therapy (ORT), 45% oral rehydration solution (ORS), and 64% continued feeding. In Kibera, 75% provided ORT, 43% ORS, and 46% continued feeding. Seeking care at a health facility, risk perception regarding death from diarrhea, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
28
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 22 publications
3
28
2
Order By: Relevance
“…This information helps to explain findings from the cross-sectional study carried out in the same sites, which showed that caregivers who gave ORT were more likely to have sought care from a health facility than caregivers who did not give ORT. 21 In sharp contrast, in countries such as Bangladesh where more than 75% of children with diarrhea are reported to be given ORS, caregivers take initiative to obtain ORS from informal providers such as chemists and shopkeepers and to administer ORT independently and manage diarrhea episodes at home. 23 Our data highlight that because of the perceived seriousness of diarrhea illnesses in young children, the first priority of caregivers was to stop the diarrhea.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This information helps to explain findings from the cross-sectional study carried out in the same sites, which showed that caregivers who gave ORT were more likely to have sought care from a health facility than caregivers who did not give ORT. 21 In sharp contrast, in countries such as Bangladesh where more than 75% of children with diarrhea are reported to be given ORS, caregivers take initiative to obtain ORS from informal providers such as chemists and shopkeepers and to administer ORT independently and manage diarrhea episodes at home. 23 Our data highlight that because of the perceived seriousness of diarrhea illnesses in young children, the first priority of caregivers was to stop the diarrhea.…”
Section: Discussionmentioning
confidence: 99%
“…In-depth interviews were carried out with the primary caregivers of children less than five years old who had recently experienced diarrhea and were interviewed in a cross-sectional survey also implemented in Asembo and Kibera. 21 Using the positive/negative deviance approach, we used purposive sampling to identify caregivers who had used ORT and continued feeding (positive behavior) and those who did not administer ORT and did not continue feeding (negative behavior) when caring for a child during a recent diarrheal episode. Diarrhea was defined as experiencing three or more watery or loose stools over a 24-hour period.…”
Section: Methodsmentioning
confidence: 99%
“…Some studies have found that maternal perception of the causes of diarrhea, perception of ORT usefulness, barriers regarding its preparation were associated with ORT use [14-16]. Other studies indicated the relationship of ORT use with maternal education, residence, income of the household and age of the patient [15,17-19]. …”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have indicated that caregivers sometimes use more than one intervention for treating diarrhea, and zinc has joined a number of interventions available to caregivers [5]. As with other interventions, zinc is not always used in isolation or just with ORS.…”
mentioning
confidence: 99%